Hubungan Indeks Massa Tubuh (IMT) dengan Aktivitas Fisik pada Mahasiswa Kedokteran - Resky Karnita Dewi; Windy Nurul Aisyah (Yayasan Citra Cendekia Celebes, 2021)
Background and Objectives: Body Mass Index (BMI) is a parameter established by WHO (World Health Organization) as a ratio of body weight to body height squared. Physical activity according to WHO is any body movement produced by skeletal muscles that require energy. Lack of physical activity) is an independent risk factor for chronic disease, and is thought to cause death globally. The aim of this study was to determine the relationship between BMI and physical activity. Methods: This study is a descriptive research design. The data was collected by using a questionnaire. The data of this study were categorical variables from 2 groups so it used the Chi-Square test. Reference results were entered into the Mendeley application using the Vancouver system. Results: total sample was 104 people with a mean age of 21-23 years. 21 years 22 people (21.2%), 22 years 46 people (44.2%), 23 years 23 people (22.1%). Based on gender, it was found that there were 37 men (35.6%) and 67 women (64.4%). Based on BMI, it was found that 13 people were underweight (12.5%), 45 people were normal (43.3%), 24 people were overweight (23.1%), 20 people were obese 1 (19.2%), and 2 people were obese 2 ( 1.9%). Conclusion: There is no relationship between BMI and physical activity.